Obesity-Associated Alterations in Inflammation, Epigenetics, and Mammary Tumor Growth Persist in Formerly Obese Mice - Rossi, Emily L.; de Angel, Rebecca E.; Bowers, Laura W.; Khatib, Subreen A.; Smith, Laura A.; Van Buren, Eric; Bhardwaj, Priya; Giri, Dilip; Estecio, Marcos R.; Troester, Melissa A.; Hair, Brionna Y.; Kirk, Erin L.; et al. (Cancer prevention research (Philadelphia, Pa.), 2016)
Using a murine model of basal-like breast cancer, we tested the hypothesis that chronic obesity, an established breast cancer risk and progression factor in women, induces mammary gland epigenetic reprogramming and increases mammary tumor growth. Moreover, we assessed whether the obesity-induced epigenetic and protumor effects are reversed by weight normalization. Ovariectomized female C57BL/6 mice were fed a control diet or diet-induced obesity (DIO) regimen for 17 weeks, resulting in a normal weight or obese phenotype, respectively. Mice on the DIO regimen were then randomized to continue the DIO diet or were switched to the control diet, resulting in formerly obese (FOb) mice with weights comparable with control mice. At week 24, all mice were orthotopically injected with MMTV-Wnt-1 mouse mammary tumor cells. Mean tumor volume, serum IL6 levels, expression of proinflammatory genes in the mammary fat pad, and mammary DNA methylation profiles were similar in DIO and FOb mice and higher than in controls. Many of the genes found to have obesity-associated hypermethylation in mice were also found to be hypermethylated in the normal breast tissue of obese versus nonobese human subjects, and nearly all of these concordant genes remained hypermethylated after significant weight loss in the FOb mice. Our findings suggest that weight normalization may not be sufficient to reverse the effects of chronic obesity on epigenetic reprogramming and inflammatory signals in the microenvironment that are associated with breast cancer progression. Cancer Prev Res; 9(5); 339–48. ©2016 AACR.